2021
DOI: 10.3390/nu13092945
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Efficacy and Mechanism of Lycium barbarum Polysaccharide against Lead-Induced Renal Injury in Mice

Abstract: Lead is one of the most common heavy metal pollutants in the environment. Prolonged exposure to lead will induce oxidative stress, inflammation, and apoptosis in the kidneys, which in turn causes kidney injury. Lycium barbarum polysaccharide (LBP) is well known for its numerous pharmacological properties. This study aims to explore the efficacy and mechanism of LBP against lead-induced kidney damage in mice. Symptoms of renal injury were induced in mice by using 25 mg/kg lead acetate (PbAc2), and different dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 68 publications
2
7
0
Order By: Relevance
“…The kidneys were the organ which suffered the most within this study, evidencing signs of inflammation, altered blood supply, and direct tubular injury, which is all in agreement with previous findings and nephrotoxic effects of lead and cadmium 48 , 49 . Within the mice treated with Chitosan@DOTAGA, the kidneys exhibited no signs of inflammation or tubular injury.…”
Section: Discussionsupporting
confidence: 92%
“…The kidneys were the organ which suffered the most within this study, evidencing signs of inflammation, altered blood supply, and direct tubular injury, which is all in agreement with previous findings and nephrotoxic effects of lead and cadmium 48 , 49 . Within the mice treated with Chitosan@DOTAGA, the kidneys exhibited no signs of inflammation or tubular injury.…”
Section: Discussionsupporting
confidence: 92%
“…UA is the end product of purine metabolism, 45 and CREA is a product of the catabolism of muscle creatine. 46 When kidney damage occurs, CREA and UA cannot be got into the urine and accumulated in the body. Serum UA and CREA levels can be used as marker indexes for kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…41 Under normal circumstances, Keap1 anchors Nrf2 in the cytoplasm and prevents Nrf2 from transferring allosterically to the nucleus. 43 One study showed that L barbarum polysaccharide had a protective effect against lead-induced kidney injury in rats by activating the Nrf2 pathway, 44 and another study showed that baicalin activated the Nrf2 pathway to have a protective effect against CCl 4 -induced acute liver damage in mice. 45 Our results showed that compared with the CON group, CCl 4 induced a decrease in the expression of Nrf2 mRNA, HO-1 mRNA, NQO1 mRNA, Nrf2 protein, HO-1 protein, and NQO1 protein and increased expression of Keap1 protein in rat liver.…”
Section: Discussionmentioning
confidence: 99%